“One-for-All” approach: a black technology for nanomedicine development? - Xiang Jiajia; Shao Shiqun; Zhou Zhuxian; Shen Youqing (Medical Review, 2023)
Cancer nanomedicines require different, even opposite, properties to voyage the cascade drug delivery process involving a series of biological barriers. Currently-approved nanomedicines can only alleviate adverse effects but cannot improve patient survival because they fail to meet all the requirements. Therefore, nanocarriers with synchronized functions are highly requisite to capacitate efficient drug delivery and enhanced therapeutic efficacies. This perspective article summarizes recent advances in the two main strategies for nanomedicine design, the All-in-One approach (integration of all the functions in one system) and the One-for-All approach (one functional group with proper affinity enables all the functions), and presents our views on future nanomedicine development.